Somatic instability of the expanded CTG triplet repeat in myotonic dystrophy type 1 is a heritable quantitative trait and modifier of disease severity - Higham, Catherine (2012)
artículo (arbitrado) -- Universidad de Costa Rica. Instituto de investigaciones en Salud, 2012. Este artículo es privado debido a limitaciones de derecho de autor.